A Bibliometric Analysis of Social Actions Investigated using DiscourseHistorical Approach - Jiin Yih, Yeo; Su Hie, Ting; Collin, Jerome; Hugh John, Leong (Universiti Malaysia Pahang Al-Sultan Abdullah Publishing, 2025)
This study examines the research landscape of social actions investigated using a bibliometric analysis of publications indexed in the Scopus database from 2002 to 2023. VOSviewer was used to visualise and analyse network maps of co-authorship and the co-occurrence of authors’ keywords related to DHA. The results reveal that the United Kingdom is a key contributor to DHA research, largely due to the prolific publications of Ruth Wodak, the approach’s proponent, from Lancaster University, along with contributions from her former students, Boukala and Forchtner. DHA research has expanded to 59 countries, reflecting its growing influence. However, co-authorship data indicate that research within this field remains largely confined to institutional and geographical boundaries, with collaborations involving only 13 countries. Building upon Reisigl’s review of DHA’s four phases of development, we present Phase Five (2017-2023) as a period when DHA research expands from evergreen areas (nationalism, national identity, populism, ideology and racism) in political discourse and media discourse into interdisciplinary approaches to investigate contemporary issues in social media discourse. A way forward for DHA research is application of the holistic framework involving analysis of all five discursive strategies to understand how language is used to achieve particular social, political, psychological or linguistic goals instead of selectively focusing on argumentation strategies and topos/topoi